Analisis Segmenting, Targeting, Positioning (STP) Terhadap Kepuasan Konsumen Pada Produk Kerupuk Buah UD. Sukma Cap MD Desa Sumber Makmur Kec. Takisung Kab. Tanah Laut Kal-Sel - Meldayanoor Meldayanoor; Muhammad Indra Darmawan; Evi Nurinayah (Jurnal Teknologi Agro-Industri, 2019)
Crackers are snack products made from tapioca starch dough or the addition of other permitted food stuffs. Crakers are widely known to have a distinctive taste and cn be accepted by everyone. The level and type needs and desires of the consumer can be different from one another, which led to the choice of opening up business opportunities became more and more bigger, election reasons and election objectives and factors to be considered in a business venture on each consumer are also different. Other that, determine which segments the market shares are located and identify consumers into segments of a particular segment as well as identify targets what is achieved and its position. In order to support the success of research to be conducted in the cracker processing industry UD. Sukma CAP MD which is where the first step of the research to be done before doing the research is a literature study to find a reference about segmentation analysis, targeting, positioning to consumer satisfaction and using descriptive analysis method, test validity, test reliability, test normality data, multiple linier regression analysis and co efficient of determination. The results showed that the test validity and reliability test on the data processed to produce valid and real data, with multiple linier regression values of vaue Y = -0,8266 + 0,3452x1+ 0,3795x2 + 0,1333x3 + 0,0904x4 and coefficient of determination () greatest 0,4624%. This shows that 46,24% great customer loyalty. Value of determination of 0,4624% ahows that the product of independent variables is considered to have only a small simultaneous effect on the dependent variable.